1989
DOI: 10.1203/00006450-198908000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Concentration in Umbilical Cord Blood of Newborn Infants after Vaginal Delivery and Cesarean Section

Abstract: ABSTRACT. Umbilical blood was collected immediatelyat birth (<30 s) in full-term infants after vaginal deliveries (n = 33) and elective cesarean sections (n = 11). Blood gases, plasma adenosine, hypoxanthine, and catecholamine concentrations were determined. In vaginally born infants the median arterial adenosine concentration was found to be 0.46 pM (range 0.13-2.06) and the venous 0.48 pM (0.09-1.62). These levels were significantly higher ( p < 0.01) than in infants delivered by elective cesarean section; 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…This parallels the postnatal fall in circulating concentrations of cortisol, placental steroids, prostaglandins, and adenosine, which are potent inhibitors of neonatal innate immune responses (9)(10)(11)(12)46). The expression pattern of MIF in newborns is unique in the sense that MIF reaches blood levels that are at least 10-fold higher than those measured in healthy children and adults, an observation that has no antecedent for a proinflammatory cytokine or mediator (7,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This parallels the postnatal fall in circulating concentrations of cortisol, placental steroids, prostaglandins, and adenosine, which are potent inhibitors of neonatal innate immune responses (9)(10)(11)(12)46). The expression pattern of MIF in newborns is unique in the sense that MIF reaches blood levels that are at least 10-fold higher than those measured in healthy children and adults, an observation that has no antecedent for a proinflammatory cytokine or mediator (7,13).…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the placenta and the fetal adrenal gland produce mediators that influence fetal and neonatal immune responses. Adenosine plasma concentrations at birth range between 0.02 and 2 μM, which is threefold higher than levels measured in adults (9,46). Concentrations of PGE 2 range between 0.4 and 10 nM at birth and decrease by fourfold during the first week of life (12, 59).…”
Section: Discussionmentioning
confidence: 99%
“…Only Irestedt et al 10 investigated the effect of mode of birth on hypoxanthine. In this study, hypoxanthine levels were shown to be significantly higher in infants born vaginally, but no measures of xanthine, uric acid or MDA levels were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although umbilical cord uric acid levels [7][8][9] and hypoxanthine levels 10 have been reported in normal term newborns, there are currently no published baseline levels of all three breakdown products of ATP as well as MDA in the cord blood of normal term infants immediately after birth. In addition, the specific effects of oxytocin-augmentation on purine and MDA levels have not been measured.…”
Section: Introductionmentioning
confidence: 99%
“…In general, PCS are considered less stressful for the fetus as compared to VD due to lower cord blood levels of the stress indicators cortisol, catecholamines, and β-endorphin [17][18][19][20][21][22]. There is also evidence that vaginal deliveries are associated with an increased oxidative stress [10] compared to c-sections.…”
Section: Discussionmentioning
confidence: 99%